Transformative change and real utopias in early childhood education : a story of democracy, experimentation and potentiality - Moss, Peter, 1945- (Contesting early childhood series, 2014)
"Early childhood education and care is a major policy issue among national governments and international organisations, promising high returns on social investment. Policy discussions are dominated by one model of provision, infused by neoliberal thinking, which constructs a formula of 'high quality', standardised goals and competition. This ground-breaking new book explores an alternative: an early childhood education and care with democracy and experimentation as fundamental values, providing a public space for citizens, young and adult, to encounter and create many projects, creating a collective workshop of many possibilities"--Resumé vydavatele